Novel application of drug-coated balloons in coronary heart disease: A narrative review - Wang, Lijin; Li, Xiaokang; Li, Tian; Liu, Lin; Wang, Haiyan; Wang, Chiyao (Frontiers in Cardiovascular Medicine, 2023)
The incidence of coronary heart disease (CAD) has soared over the years, and coronary intervention has become an increasingly important therapeutic approach. The past decade has witnessed unprecedented developments in therapeutic medical instruments. Given that drug-coated balloons bring many benefits, they are indicated for an increasing number of conditions. In this article, we review the results of current clinical trials about drug-coated balloons and summarize their safety and clinical progression in different coronary artery diseases, laying the groundwork for basic research, and clinical therapeutics of this patient population.